(untitled) (CIPEEX, 2025)
This cross-sectional analytical observational study investigates the impact of electronic cigarette use on respiratory muscle strength in young adults. The research was conducted with 70 medical students from UniEVANGÉLICA, divided into two groups: electronic cigarette users and non-users. The body mass index (BMI), maximum inspiratory pressure (MIP), and maximum expiratory pressure (MEP) were evaluated through respiratory maneuvers. The results showed that electronic cigarette users had significantly higher values of Pimax (p=0.04) and Pemax (p=0.002), indicating superior inspiratory and expiratory respiratory function compared to non-users. Despite this, the percentages of Pimax and Pemax did not show a significant difference. The study contributes to the understanding of the effects of electronic cigarettes on the respiratory health of young adults.